PERENCANAAN STRUKTUR GEDUNG RUSUNAWA DI KABUPATEN SUKOHARJO DENGAN SISTEM RANGKA PEMIKUL MOMEN KHUSUS - Harris Ian Masdhuki; Kusdiman Joko Priyanto; Teguh Yuono; Kukuh Kurniawan Dwi Sungkono; Chia Soi Lee (Civil Engineering, Faculty of Engineering, Universitas Tunas Pembangunan Surakarta, 2026)
The rapid population growth in the city of Sukoharjo and the increasing selling value of land, the construction of flats is the fulfillment of the need for housing.